Novel Passive Vector-Sum Reconfigurable Filtering Phase Shifter With Continuous Phase-Control and Tunable Center Frequency - Zhu, Xu; Yang, Tao; Chi, Pei-Ling; Xu, Ruimin (IEEE transactions on microwave theory and techniques, 2022)
In this article, a novel reconfigurable filtering vector-sum phase shifter (RFPS) with a continuous phase shift range of \ge 300^{° } and tunable operating frequency range from 1.05 to 1.3 GHz is proposed. It consists of two identical wideband Wilkinson power dividers (or power combiners) (WPDs) and a reconfigurable filtering quadrature coupler (RFQC) that is connected between the two WPDs. Through the first WPD, the split waves are fed into the RFQC and are then combined at the output ports of the RFQC. The phase of the combined waves can be continuously tuned by adjusting different combinations of coupling types between interstage resonators of the RFQC, and the resulted output waves are then summed up through the second WPD with the desired output phase. Different from the conventional active vector-sum phase shifter, the vector summing is realized by the proposed RFQC and is a pure passive design, resulting in a low-cost, low-noise, easy-design, and highly flexible system. A prototype is designed and fabricated to demonstrate the proposed technique. Detailed theoretical analysis and design procedure have been given. The experimental results show that the proposed RFPS features the continuous phase-control range of more than 300° with a tunable filtering response covering the frequency range from 1.05 to 1.3 GHz.